Mineralogy, petrology, and petrogenesis of the Suvasvesi granitoid intrusion - Rantanen, Hanna (Helsingin yliopisto, 2021)
The Paleoproterozoic (1.87 Ga, ɛNd -3.7) Suvasvesi granitoid intrusion in southeastern Finland is considered to be a part of the Heinävesi intrusive suite. Inner parts of the lithologically zoned Suvasvesi intrusion are variably alkali feldspar porphyritic biotite granitoid rock and the margins are composed of a more biotite-rich equigranular granitoid rock variety. The Paleoproterozoic metasedimentary rocks of the Viinijärvi suite adjacent to the Suvasvesi intrusion are intruded by leucocratic pegmatite dikes. Potential sources and possible contamination of the granitoid melt are considered with the help of structural and textural observations, petrography, whole-rock geochemistry, mineral chemistry, and petrophysical data. The data were acquired from 34 rock samples collected during a bedrock mapping campaign and combined with the pre-existing mapping, petrographic, and geochemical data from the Suvasvesi and surrounding areas. The Suvasvesi granitoid intrusion is compared to other members of the Heinävesi suite to verify the hypothesis of their petrogenetic connection. The compositions of both Suvasvesi intrusion and Heinävesi suite are also compared to the potential proximal sources, the adjacent Paleoproterozoic metasedimentary rocks and Archean units in the area. In addition, the compositions of the Suvasvesi intrusion and Heinävesi suite rocks are compared to other granitoids from Eastern and Northern Finland with suggested Archean sources, and to regional granitoids of same age. Based on the similarity of major and trace element compositions, it is suggested that the Suvasvesi granitoid is part of the Heinävesi suite. The granites and granodiorites of the Suvasvesi granitoid and the Heinävesi suite are ferroan, calc-alkalic, and peraluminous with average ASI value of 1.08 (n = 73). Although the Heinävesi suite is postkinematic, it shows very few similarities to other rocks of same age. The εNd values of the Heinävesi suite and the paragneiss enclaves within the Suvasvesi intrusion indicate ...